Fórmulas do tipo Heron - Fernandes, Thiago Andrade (2021)
This work aims to cataloge demonstrations for Heron formula and discusses Herontype formulas. This study is pertinente because, in literature, we do not find works that agglutinate several demonstrations of the famous Heron formula, in relevant quantity and from different branches of mathematics, nor that bring a mapping or point out a definition for the expression Heron-type formulas. Therefore, we started with a biographical research on Heron and his works, with emphasis on the work called Metric, as well as highlighting his inventor side and listing his studies focused on mechanics. In the sequence, we deal with a series of demonstrations for the wellknown “Heron's formula”, which calculates the area of a triangle based on the measure of its three sides. Int the end, we list some examples for Heron-type formulas, with their respective demonstrations. Based on the visualization of this compilation, we developed an attempt to define the Heron-type formula expression.